Bioactive terpenoids from Euphorbia pubescens: isolation and derivatization - Carréu, João Paulo Magalhães (2020)
Tese de mestrado, Química Farmacêutica e Terapêutica, 2020, Universidade de Lisboa, Faculdade de Farmácia.